Morphological variants of plasma cell myeloma: a case series of diagnostic mimics - Abdul Halim, Sarah; Mohd Nasiruddin, Dhamirah Nazihah; A.Talib, Norlelawati (2025)
Introduction: Plasma cell myeloma (PCM) exhibits notable morphological heterogeneity beyond the classical plasma cell phenotype. Recognition of these variants is critical for accurate diagnosis and avoiding misclassification, particularly when they mimic other haematological or non-haematological malignancies. We report three PCM cases with distinct morphological features posing diagnostic challenges. Case Series: Case 1: A 65-year-old woman with multiple lytic skull lesions. Bone marrow examination revealed large cells with irregular, lobulated nuclei and abundant basophilic cytoplasm with vacuoles and blebs, morphologically resembling monocytes. immunohistochemistry (IHC) demonstrated CD138 positivity, kappa light chain restriction, and aberrant CD56 and CD117 expression. Case 2: A 62-year-old woman with renal impairment and reversed albumin-to-globulin ratio showed marrow infiltration by plasmablasts with high nuclear-to-cytoplasmic ratios, dispersed chromatin, and prominent nucleoli. Trephine biopsy revealed sheets of CD138-positive plasma cells with kappa light chain restriction. Case 3: A 66-year-old man with relapsed PCM and a concurrent neuroendocrine tumour of the nasopharynx demonstrated bone marrow involvement by pleomorphic, large sized, basophilic cells with cytoplasmic blebs. An initial impression of metastatic infiltration was revised following trephine biopsy, which showed sheets of CD138+, MUM1+, CD56+ plasma cells with kappa restriction; cytokeratin AE1/AE3 was negative. Discussion: This case series highlights the morphological diversity of PCM, which may mimic other neoplastic processes. Reliance on morphology alone may lead to misclassification. A combination of careful morphological assessment, supported by immunophenotyping and clinical correlation is essential for accurate diagnosis and prevent delays in treatment.